HUBUNGANÂ FUNGSI KELUARGA DENGAN KUALITAS HIDUPÂ LANSIA HIPERTENSI USIA LEBIH DARI 60 TAHUN DI DUSUNÂ PASINAN KRAJANDESASEKARGADUNG KECAMATANPUNGGING KABUPATEN MOJOKERTO - Akbar, Amar; Wibowo Suganda, Tri (JURNAL KEPERAWATAN BINA SEHAT, 2016)
Elderly patients with hypertension takes the role of the family in helping the elderly, each family member to support each other indicates that the function in the family goes well. A well-functioning family will make the steps used to solve the problem in advance, discuss the problems, these problems communicating with each other, and determine appropriate action so that elderly people with hypertension can have a good quality of life. The purpose of this study was to determine the relationship of family functioning and quality of life of elderly patients with hypertension. The research design used in this study is an analytic correlation with cross sectional approach. The population of elderly aged over 60 years and obtained a sample of 37 respondents using simple random sampling technique independent variables in this study was a family function and dependent variable is the quality of life of the elderly. family function was measured by the Family Function Device (FAD) and the quality of life measured by WHOQOL BREEF.Hasil research shows that a family function and quality of life of elderly hypertensive patients aged over 60 years in the hamlet pasinan Krajan village districts sekargadung Pungging mojokerto district has a value of ρ = 0 , 00 <α 0:05. Analyzed using contingency coefficient test with a significant level of 0.00. Shows that the correlation between the two variables is high enough to sense the better function of the family that owned the higher the quality of life in lansia.Lansia with hypertension require the participation of others such as the role of family members in helping the elderly, each family member to support each other indicates that the function family and healthy family environment is closely related to the quality of life of the elderly.Keywords: Elderly, Family Function, Quality of Life